2005
DOI: 10.1590/s0100-879x2005000300014
|View full text |Cite
|
Sign up to set email alerts
|

Late-life depression, heart failure and frontal white matter hyperintensity: a structural magnetic resonance imaging study

Abstract: The relevance of the relationship between cardiac disease and depressive symptoms is well established. White matter hyperintensity, a bright signal area in the brain on T2-weighted magnetic resonance imaging scans, has been separately associated with cardiovascular risk factors, cardiac disease and late-life depression. However, no study has directly investigated the association between heart failure, major depressive symptoms and the presence of hyperintensities. Using a visual assessment scale, we have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…For the most part, the relationships with respect to the cognitive and MRI were theoretically consistent as one would expect attention, executive, and psychomotor function to be most affected in patients with greater WMH (Almeida et al, 2005;Bakker et al, 1999;Breteler et al, 1994;Chalela, Wolf, Maldjian, & Kasner, 2001;R. Cohen, 1993;R.…”
Section: Discussionsupporting
confidence: 53%
“…For the most part, the relationships with respect to the cognitive and MRI were theoretically consistent as one would expect attention, executive, and psychomotor function to be most affected in patients with greater WMH (Almeida et al, 2005;Bakker et al, 1999;Breteler et al, 1994;Chalela, Wolf, Maldjian, & Kasner, 2001;R. Cohen, 1993;R.…”
Section: Discussionsupporting
confidence: 53%
“…Indeed, this study found depression was associated with reduced baseline cognitive function in each domain, which is consistent with past cross-sectional studies examining this link in HF (Garcia et al, 2011; Pullicino et al, 2008). Depression in HF may represent a neuropsychiatric change secondary to underlying brain pathology, including white matter lesions of the frontal brain regions (Almeida et al, 2005) and such mechanisms are also thought to underlie cognitive impairment in HF (Hoth, 2010). Our findings showed that depression remained stable over time, which indeed may be attributed to minimal changes in neuropathology or disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot exclude that this factor contributed to our failure to demonstrate the hypothesized association between SSD and WML. Lastly, we averaged WML volumes over the whole brain to evaluate the relationship of white matter abnormalities and SSD which might be a less specific measure than regional WMSH volumes given that previous studies have shown that frontal WML may have stronger associations with depressive symptoms than WMSH in other brain regions (41).…”
Section: Discussionmentioning
confidence: 99%